Effects of kangaroo and routine care on physiologic parameters of low-birth-weight infants - Nurian, M; Mashdberd, Y; Yaghmaei, F; Akbarzadeh Baghbani, A.R; Heydarzadeh, H (Advances in Nursing & Midwifery, 2009)
Background and aim Low birth weight (LBW) is the most important indicator of mortality in children. These infants cannot tolerate physiologic stresses; therefore, they are isolated from their mothers to be put in incubators. This isolation put them at numerous risks. This clinical trial was conducted to compare the effects of kangaroo with routine care on physiologic parameters of low-birth-weight infants at NICUs in 2008. Materials and methods 80 LBW infants were randomly divided into 2 equal experimental and control groups. In kangaroo-care group, the infants were removed from incubator for 1 hour and put on the chest of their mothers. The control group was provided care routinely. Physiologic parameters including pulse rate, oxygenation of arterial blood, temperature and respiratory rate were checked at 30 and 50 minutes after the return of infants to their incubators. Data collection form was validated by content method and validities of instruments were checked by choosing standard and authorized devices. Reliability was achieved by inter-rater method (r=0.87). Findings No significant difference was found between the 2 methods during care in terms of the parameters (P>0.05). However, a significant difference was found between pulse rate as well as oxygenation changes 5 and 50 minutes after care delivery (P=0.01, P=0.02 and P=0.03) with no difference in temperature (P=0.48). Conclusion Findings showed that Kangaroo care is as effective as routine care in stability of physiologic parameters. Therefore, developing educational programs for healthcare personnel, nurses and mothers can facilitate the provision of this type of care. Keywords: Physiologic parameters, Low-birth-weight infants, Kangaroo care, Routine care, Neonatal intensive care units (NICUs). *Corresponding Author: Nurian, M; Dept. of Pediatrics, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences . Tehran, Iran. E-mail: Manighea@yahoo.com